2020
DOI: 10.3906/sag-1906-78
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the National Early Warning Score (NEWS) at the time of discharge from the intensive care unit

Abstract: The discharge of critical care patients from the intensive care unit (ICU) to the general ward without delay helps to reduce costs and enables the reasonable use of the valuable ICU beds [1]. However, transferring patients who require care following their stay in ICU before they are ready for the general ward increases the probability of their readmission into ICU [2]. Reportedly, readmitted patients have higher mortality and length of stay at the hospital and ICU [3,4]. Moreover, readmission rates are current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
1
0
2
Order By: Relevance
“…Our findings coincide with many similar studies. Consistent with this study, many previous studies have shown the NEWS and MEWS scores to be a decisive tool for the early identification of patients with a high risk of poor outcomes, including mortality and ICU readmission ( 32 34 ). Balshi et al reported that the MEWS is associated with ICU readmission, and a score > 6 has an excellent accuracy as a prognostic predictor ( 32 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings coincide with many similar studies. Consistent with this study, many previous studies have shown the NEWS and MEWS scores to be a decisive tool for the early identification of patients with a high risk of poor outcomes, including mortality and ICU readmission ( 32 34 ). Balshi et al reported that the MEWS is associated with ICU readmission, and a score > 6 has an excellent accuracy as a prognostic predictor ( 32 ).…”
Section: Discussionsupporting
confidence: 89%
“…Klepstad et al showed that the higher NEWS in gastrointestinal surgical patients at ICU discharge was the predictive factor of ICU readmission ( 33 ). Moreover, the study by Doðu et al demonstrated that a NEWS value of >7.5 at the time of discharge from ICU estimates a high probability of ICU readmission within the first 48 h after discharge ( 34 ). However, in contrast to these findings, a study by Reini et al showed that the MEWS at ICU discharge is not a predictor of ICU readmission ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kết quả nghiên cứu của chúng tôi cho thấy tuổi người bệnh có liên quan có ý nghĩa thống kê với sự xuất hiện tình trạng suy giảm lâm sàng sớm, kết quả nghiên cứu của chúng tôi cũng tương đồng với một số kết quả nghiên cứu khác [7][8][9][10] Hình thức sử dụng vận mạch cũng cho thấy mối liên quan có ý nghĩa thống kê với sự xuất hiện tình trạng suy giảm lâm sàng sớm. Kết quả nghiên cứu của chúng tôi cũng tương đồng với kết quả nghiên cứu của tác giả Ponzoni được tiến hành năm 2017 tại Brazil [6,10] Kết quả nghiên cứu của chúng tôi cho thấy giới tính không có mối liên quan có ý nghĩa thống kê với sự xuất hiện của tình trạng suy giảm lâm sàng sớm.…”
Section: Các Yếu Tố Liên Quan đếN Sự Xuất Hiện Tình Trạng Xấu đI Sớm ...unclassified
“…quả nghiên cứu cho thấy tuổi, điểm NEWS khi xuất ICU và có sử dụng vận mạch hay không đều dự đoán có ý nghĩa thống kê với tình trạng này. Kết quả nghiên cứu của chúng tôi cũng tương đồng với một số nghiên cứu khác[1,6,7,10]. Kết quả nghiên cứu của chúng tôi cho thấy người bệnh tuổi cao, có điểm NEWS cao, sử dụng vận mạch khi xuất ICU được cho là những người bệnh có nguy cơ cao bị xấu đi sớm trên lâm sàng sau khi rời khỏi ICU.…”
unclassified